Utopias of the Text: Pre-Figurations of the Post-Literary. Issue 1 (April 2019) - Noys, Benjamin
Abstract : Utopias of the text are the moments of the emergence of a new and radical concept of the text as overflowing all limits and boundaries. Here these utopias are traced in the writings of Roland Barthes, Jacques Derrida, and Michel Foucault. They often emerge at the margins of these texts, in fragments or boundaries at which the utopia can be glimpsed before disappearing. These utopian moments can be reconstructed as a form of thinking the post-literary and its limits. They can also be traced to the explosion of speech during May 1968 and Maurice Blanchot is a key figure who links together this political moment with the 'neutral' form of writing. This article explores the fading of these utopias of the text alongside this draining of political energies. These processes of critique and waning suggest the inversion of utopias of the text into dystopias of the text. Now the sign or signifier appears dispersed or even insignificant compared to the powers and forces of post-literary domination. In this situation, however, the article suggests, the persistence of the utopias of the text as a critical horizon that can still inform how we grasp the equivocations of our post-literary moment.